2019
DOI: 10.1042/bsr20190602
|View full text |Cite
|
Sign up to set email alerts
|

SOX21-AS1 is associated with clinical stage and regulates cell proliferation in nephroblastoma

Abstract: LncRNA SOX21 antisense RNA 1 (SOX21-AS1) dysregulated in many types of human cancer, and functioned as tumor suppressor or promoter depending on tumor types. However, there was no report about the role of SOX21-AS1 in nephroblastoma. In the present study, we first found that SOX21-AS1 expression was elevated in nephroblastoma tissues and cell lines compared with adjacent normal tissues and normal human embryonic kidney cell line, respectively. Moreover, we observed nephroblastoma patients with large tumor size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…For example, SOX21-AS1 participates in cervical cancer progression by competitively binding miR-7/voltage dependent anion channel 1 ( 57 ), while it sequesters miR-145 in CRC, which promotes tumor progression via the enhanced expression of myosin VI ( 60 ). SOX21-AS1 knockdown in nephroblastoma cells in vitro disrupts the proliferation and colony formation of these cells through a mechanism associated with p57 upregulation, and results in cell cycle arrest ( 62 ). In addition, SOX21-AS1 is associated with HCC progression and patient prognosis via a mechanism associated with p21 epigenetic silencing ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, SOX21-AS1 participates in cervical cancer progression by competitively binding miR-7/voltage dependent anion channel 1 ( 57 ), while it sequesters miR-145 in CRC, which promotes tumor progression via the enhanced expression of myosin VI ( 60 ). SOX21-AS1 knockdown in nephroblastoma cells in vitro disrupts the proliferation and colony formation of these cells through a mechanism associated with p57 upregulation, and results in cell cycle arrest ( 62 ). In addition, SOX21-AS1 is associated with HCC progression and patient prognosis via a mechanism associated with p21 epigenetic silencing ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…The previous study has been shown that the nonmuscle myosin light chain kinase isoform, cloned from MYLK gene, was found highly expressed in an endothelial cell in lung cancer (Adyshev et al, 2013). Another study has also shown that lncRNA SOX21 antisense RNA 1 was elevated in tissue and cell lines of nephroblastoma in comparison with adjacent normal tissues and cell line of the healthy human embryonic kidney (Zhang et al, 2019). In addition, MYLK‐AS1 is also elevated in hepatocellular carcinoma and also engaged in higher risk of death (Ye et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…63 SOX21-AS1 has been linked to tumor progression and defined as a prognostic marker in cervical cancer, nephroblastoma, hepatocellular carcinoma, and lung and oral cancer. [64][65][66][67][68][69] In glioblastoma, SOX21-AS1 was defined along other four lncRNAs as a signature that predicts survival. 70 CRNDE is an important oncogenic lnRNA implicated in multiple malignancies including glioblastoma.…”
Section: Discussionmentioning
confidence: 99%